Estudos limnológicos e ecotoxicológicos (laboratoriais e in situ), com ênfase na avaliação da toxicidade de metais e de pesticidas organoclorados em peixes (Danio rerio e Poecilia reticulata - sub-bacia do rio Monjolinho (São Carlos SP) - Fracácio, Renata (2006)
In order to evaluate the physical, chemical, biological and ecotoxicological parameters of Monjolinho River system (in laboratory and in situ), water and sediment samples (from the river and from eight of its tributaries) we obtained in july/03, October/03, January/04 and April/04. Juveniles and adult individuals of Danio rerio and Poecilia reticulata were used in the ecotoxicological studies. Mortality, juvenile biometry, and deletery effects observed on the gills tissue were considered in the tests. The limnological data revealed the higher concentrations of heavy metals and organochlorides in the dry season, being over the limits established for aquatic organisms protection. The concentrations of zinc and heptachlore found in the sediments of the last study sites resulted in deletery effects. The higher concentrations of the analyzed parameters were found in the study sites UFSCar, Confluência and Córrego Tijuco, probably due to the higher concentrations of clay and silt found in these areas. The partially chronic tests performed using samples obtained from the natural environment revealed significant toxicity for at least one fish species and one parameter. Tests in situ showed more drastic effects, especially in July/03. P. reticulata was more vulnerable when compared to D. rerio in all of the analyses, especially considering the juvenile stages. Two contaminants were used in the laboratory ecotoxicological analyzes, using D. rerio juveniles as a test organism. Cadmium showed a CL(I)50, 96h, of 1894,73µg/L. In the tests of static partial chronic toxicity, the chronic value obtained was 189,73µg/L, for both survival and growth, indicating that in the same concentration, the effects on the survival and biometry were similar. Gills morphological alterations increased with the increasing concentrations: 0.6 µg/L, 6 µg/L, 60 µg/L and 600 µg/L, being the fusion of the secondary lamellaes observed in the last concentration. Regarding to the endossulfan sulphate, the semi-static CL(I)50, 96h, was 7.24 µg/L and the chronic value, considering survival rates, was 0.948 µg/L. Histological effects were observed in all of the concentrations (0.03 µg/L, 0,3 µg/L and 3 µg/L), being the hyperplasia and secondary lamellae fusions more drastic in the last concentration. The toxicity tests, as well as the limnological analyses, showed that the Monjolinho system in highly disturbed, with inadequate conditions for the conservation of the aquatic organisms and may represent risks for the human health.